Central Bank Digital Currencies (CBDCs) as a future of financial system - Shykhman, Andrii; Taušer, Josef; de Batz de Trenquelléon, Laure Sabine Marie; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
This thesis examines the possibilities of how Central Bank Digital Currencies (CBDCs) can influence the future of the financial system and what consequences CBDCs may have on economic stability, as well as, to a broader extent, financial inclusion. The section starts with a definition of the financial system, its historical foundations and present composition, and an interpretation of the challenges it faces. The next chapter provides a comprehensive understanding of CBDCs, their theoretical foundations, and their historical significance. This paper offers a structured framework to compare different prototypes of CBDCs and assess their potential economic impact. It examines various forms of CBDCs, such as their different versions, wholesale and retail models, technical implementation, and use cases, before evaluating their potential impact on monetary policy. The case studies form a patchwork of different CBDCs from various regions (e.g., E-Naira in Namibia, Sand Dollar in the Bahamas) and illustrate some samples of potential implementation results (e.g., 12-week trial for U.S. Digital Dollar; Euro CBDC testing; China trials with e-CNY). The other kinds of case studies respond to questions or political issues and discuss strategies that can help in the process. This includes exploring the potential implications and some of the key issues related to CBDCs, highlighting aspects such as financial inclusion, privacy concerns, or security threats on cross-border payments. It also explores blockchain and its potential use for CBDC structure. The empirical part of the thesis examines expert interviews and questionnaires, delivering both quantitative and qualitative expressions of individual perceptions on chances for CBDCs.
The thesis concludes by sketching out potential long-term prospects and pragmatic guidelines for the smooth sailing of CBDCs and reiterates its conclusion about how there is a strong likelihood that CBDCs could alter the financial system in both positive and negative ways.
Vedoucí práce: Josef Taušer
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses